2009
DOI: 10.1103/physreva.80.053420
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced atom desorption for cesium loading of a magneto-optical trap: Analysis and experimental investigations

Abstract: With the help of light-emitting diodes at the center wavelength of 470 nm, we demonstrate that light-induced atom desorption ͑LIAD͒ can be used for flexibly controlling the loading of magneto-optical traps ͑MOT͒ of cesium atoms. Under an ultralow background pressure in a quartz cell without any wall coating, we show that low intensity blue light can be used to control the loading rates ͑from 200 to 4000 atoms/s͒ and the number of cesium atoms ͑on the order of 10 4 in our experiment͒ in a MOT without the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…We find a pressure decay time that is much faster than the other time scales of our experiment, comparable to Refs. [46,47]. Our observations are compatible with the scenario where almost all Na atoms stick to the surfaces of the vacuum system after a few bounces when TABLE II.…”
Section: Discussionsupporting
confidence: 85%
“…We find a pressure decay time that is much faster than the other time scales of our experiment, comparable to Refs. [46,47]. Our observations are compatible with the scenario where almost all Na atoms stick to the surfaces of the vacuum system after a few bounces when TABLE II.…”
Section: Discussionsupporting
confidence: 85%
“…LIAD rates are linearly dependent on the light intensity, which has also been reported in Ref. [16,17]. This linear dependence indicates that the observed LIAD is a one-photon process and is not caused by heating effects.…”
Section: Light-induced Atom Desorptionmentioning
confidence: 50%
“…However, most LIAD studies [13,[15][16][17][18][19] focused only on desorbed atoms, and lack of basic knowledge of the surface itself leads to a poor understanding of desorption mechanisms and also some contradictory practical information. For example, one group reported that LIAD from quartz glass is not effective [20], but another loaded a magneto-optical trap in a quartz cell by LIAD [16].Following our previous study [21], we introduce surface analysis for glass surfaces, for which LIAD measurements were then carried out by focusing on differences between vitreous silica (synthetic quartz) and commercial borosilicate glass (Pyrex), which are the most commonly used Abstract We analyzed the surfaces of vitreous silica (quartz) and borosilicate glass (Pyrex) substrates exposed to rubidium (Rb) vapor by X-ray photoelectron spectroscopy (XPS) to understand the surface conditions of alkali metal vapor cells. XPS spectra indicated that Rb atoms adopted different bonding states in quartz and Pyrex.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is obvious that the cavity transmission is only dependent on the parameter y, and the trajectory of the single atom passing through the tilted TEM 10 mode thus can be determined uniquely. The experimental setup contains two important parts, including the cold atom cloud trapped by MOT [27] and the highfinesse Fabry-Pérot cavity composed of two spherical mirrors [28,29]. Both of them are located in an ultrahigh vacuum chamber.…”
mentioning
confidence: 99%